Analysis of economic and social factors affecting the Human Development Index (HDI) in Central Java - Romadhani, Arien Ismi; Anwar, Aminuddin (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2025)
Purpose – This study aims to analyze the influence of economic and social factors on the Human Development Index (HDI) in districts and cities of Central Java Province during the period 2014–2023.Methods – The study employs a panel data regression approach to analyze variables including GRDP per capita, school participation rates at various education levels, the number of people living in poverty, and the number of healthcare facilities.Findings – The results indicate that GRDP per capita and the number of health facilities have a positive and significant impact on HDI, while poverty has a negative and significant effect. School enrollment at the primary and secondary levels shows mixed results, with senior high school enrollment positively contributing to HDI.Implication – The findings highlight the need for regional policymakers to focus on poverty alleviation, economic productivity, and the expansion of healthcare infrastructure to enhance human development outcomes.Originality – This research provides a recent and comprehensive analysis of HDI determinants at the sub-provincial level in Central Java using a panel data approach, incorporating school enrollment by level to capture nuanced educational effects often overlooked in previous studies. AbstrakTujuan – Penelitian ini bertujuan untuk menganalisis pengaruh faktor ekonomi dan sosial terhadap Indeks Pembangunan Manusia (IPM) di kabupaten/kota Provinsi Jawa Tengah pada periode 2014–2023.Metode – Penelitian menggunakan pendekatan regresi data panel untuk menganalisis variabel yang meliputi PDRB per kapita, angka partisipasi sekolah pada berbagai jenjang pendidikan, jumlah penduduk miskin, dan jumlah fasilitas kesehatan.Temuan – Hasil penelitian menunjukkan bahwa PDRB per kapita dan jumlah fasilitas kesehatan berpengaruh positif dan signifikan terhadap IPM, sedangkan tingkat kemiskinan berpengaruh negatif dan signifikan. Pengaruh angka partisipasi sekolah bervariasi; pada jenjang SMA berpengaruh positif signifikan, sedangkan jenjang lainnya menunjukkan hasil yang tidak konsisten. Implikasi – Temuan ini mengindikasikan pentingnya peran kebijakan daerah dalam mengurangi kemiskinan, meningkatkan produktivitas ekonomi, dan memperluas infrastruktur layanan kesehatan untuk mendorong peningkatan pembangunan manusia.Orisinalitas – Penelitian ini menyajikan analisis terkini dan komprehensif mengenai determinan IPM di tingkat kabupaten/kota di Provinsi Jawa Tengah dengan pendekatan data panel, serta memperhatikan pengaruh angka partisipasi sekolah berdasarkan jenjang pendidikan yang sering kali luput dalam kajian sebelumnya.